A Webquest to promote Significant Learning in Optical Isomery teaching (Research, Society and Development, 2021)
In the 21st century, it is notorious how much teenagers know how to handle digital devices, such as smartphones and tablets, which reveals the importance of including these technologies in education. Since smartphones are like an extension of the bodies of these young people, by turning them into a didactic resource, students' interest is aroused. The present study aimed to address the Isomeria Óptica content, a chemistry theme attributed by students as not important, through the Webquest tool that sought to arouse the interest of students from a third-year high school class, for better application of the research to the class. was divided into 5 groups. During the development of the activity, each group had the task of drawing a 3D drawing on a poster about the theme designated by the teacher-researcher, and then presenting the theme represented by the drawings on the poster. With this research, it was found a greater interaction and participation of students, as well as the construction of some skills such as: empathy and cooperation, digital culture, mastery of content, creativity and communication.